2005
DOI: 10.1097/01.olq.0000159211.40719.2b
|View full text |Cite
|
Sign up to set email alerts
|

Community Planning, HIV Prevention, and a Needs Assessment for Men Who Have Sex With Men: The South Beach Health Survey

Abstract: Population-based HIV antibody testing revealed a remarkably high annual incidence of HIV infection. A community-based organization was transformed to implement a social marketing campaign and provide other disease prevention services for MSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The coastal Zone III has had the second highest number of cumulative HIV cases and the fifth highest number of cumulative AIDS cases. The area includes South Beach, which is a popular tourist Mecca and has increasingly attracted the gay population since the 1990s (Holcomb and Luongo, 1996); MSM has been a major risk factor for HIV/AIDS in South Beach (Webster et al, 2005). Zone V is in North Central Dade, which has the second highest concentration of AIDS cases and the third highest concentration of HIV cases.…”
Section: Resultsmentioning
confidence: 99%
“…The coastal Zone III has had the second highest number of cumulative HIV cases and the fifth highest number of cumulative AIDS cases. The area includes South Beach, which is a popular tourist Mecca and has increasingly attracted the gay population since the 1990s (Holcomb and Luongo, 1996); MSM has been a major risk factor for HIV/AIDS in South Beach (Webster et al, 2005). Zone V is in North Central Dade, which has the second highest concentration of AIDS cases and the third highest concentration of HIV cases.…”
Section: Resultsmentioning
confidence: 99%
“…An independent study conducted in 1996 as part of a comprehensive needs assessment in Miami, Florida, detected an even higher prevalence of HIV disease (31%) among MSM living in an area known as South Beach. 2 The incidence of HIV infection among South Beach residents in 1996 was estimated to be 10% (95% CI = 5-18%). In the South Beach Health Survey, engaging in anal sex while under the influence of alcohol and/or drugs and having difficulty keeping an erection while using a condom were significant predictors of unprotected anal intercourse (UAI) with nonprimary partners.…”
Section: Introductionmentioning
confidence: 99%
“…MSM remain at high risk for acquiring HIV infection even when they are older. A cross-sectional survey of MSM residing in Florida found that almost 50% reported unprotected anal intercourse and that a significant predictor for this high-risk activity was associating the use of condoms with erectile problems [19]. The higher prevalence of erectile dysfunction among older men coupled with experiencing or perceiving that condoms will exacerbate erectile difficulties may contribute further to "condom fatigue" and heighten the risk for acquiring and transmitting HIV.…”
Section: Hiv Acquisition and Transmission Among Older Personsmentioning
confidence: 99%